DIRECTED AND SPONTANEOUS FORMATION OF ICHTHYOFAUNA IN RESERVOIRS - Nurmatova Rukhsora Utkir kizi (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
The targeted formation of the ichthyofauna of reservoirs includes the introduction, acclimatization and breeding of fish. These activities are carried out with the aim of enriching the species composition and increasing the fish productivity of reservoirs. The spontaneous formation of ichthyofauna occurs under the influence of natural processes, such as migration and settlement of fish, as well as interactions between species. This process may be the result of the unintentional or accidental introduction of new species that adapt to new conditions and begin to reproduce successfully.